Uji Pemberian Ekstrak Daun Kenikir (Cosmos Caudatus) Terhadap Aktivitas Kecoa Amerika (Periplaneta americana) - Rizqiyyati Afifah; Lina Listiana (PEDAGO BIOLOGI, 2019)
Abstract: The increasing population of American cockroaches (Periplaneta americana) which are Arthopoda vectors can transmit, move or become a source of transmission of disease on humans. Therefore, it is necessary to control the American cockroach population (Periplaneta americana) by giving vegetable insecticide from leaf extract of kenikir (Cosmos caudatus). Leaf extract of Kenikir (Cosmos caudatus) has active compounds such as essential oils, flavonoids, saponins, alkaloids, and tannins which can affect the activity of American cockroaches (Periplaneta Americana). This study aimedÂ  to (1) determine the effect of leaf extract of kenikir (Cosmos caudatus) on the activity of American cockroaches (Periplaneta americana). The type of this research was an experimental study using the Posstest-Only Control Design, consisting of 5 treatments and each design was carried out 5 times. The population of this study was American cockroaches (Periplaneta americana) obtained by the researcher from American cockroach sellers (Periplaneta americana) in the Bratang area, Surabaya City, East Java. The independent variable was the various concentrations of leaf extract of kenikir (Cosmos caudatus). While, the dependent variable was the activity of American cockroaches (Periplaneta americana). Data were analyzed using One-Way ANOVA. Based on the results of the study, it was concluded that (1) there was an effect of various concentrations of leaf extract of kenikir (Cosmos caudatus) on the activity of American cockroaches (Periplaneta americana). Â